Neutral electrocatalytic hydrogen evolution method
By using cobalt iron bimetallic phosphide nanosheet material as hydrogen evolution working electrode in neutral electrolyte, the problem of difficulty in continuous operation under high current density in the prior art is solved, and efficient and stable hydrogen evolution performance in neutral electrolytes and simulated seawater is achieved.
Patent Information
- Application Number
- CN202411406327.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to continuously work under high current density in neutral electrolytes, and the neutral electrolytic hydrogen production technology has not yet met the requirements for commercial application.
Cobalt iron bimetallic phosphide nanosheet material is used as the hydrogen evolution working electrode, neutral electrocatalytic hydrogen evolution is carried out in neutral electrolyte or neutral simulated seawater, and nanosheet material is prepared by hydrothermal reaction and high-temperature phosphating method.
At current densities of 10, 100 and 400 mA/cm2, the overpotential is significantly reduced, and it can operate stably for more than 400 hours at a constant current density of 500 mA/cm2 in neutral solution, without significant attenuation of water reduction performance.
Smart Images

Figure CN119800408A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to a neutral electrocatalytic hydrogen evolution method. Background Art
[0002] Hydrogen is an ideal green energy source with the characteristics of zero pollution, high energy, and wide sources. It will be the main energy source in the future. It is expected that the share of energy demand in 2050 will reach 34%. Hydrogen produced by water electrolysis can be driven by renewable and clean energy, which is a very clean preparation method. At present, the industry adopts the method of alkaline water electrolysis to produce hydrogen, but this method has the same problems as acidic water electrolysis, such as corrosion of the electrolysis device, resulting in poor stability and unfriendly environment. However, hydrogen production in neutral or near-neutral electrolytes can solve the above difficulties; and if the technology of neutral water electrolysis to produce hydrogen can make breakthrough progress, it is possible to make full use of the abundant weak alkaline seawater on the earth, thereby achieving cheaper and more efficient hydrogen production and promoting various commercial and industrial applications. The water electrolysis hydrogen production industry requires the catalyst to be able to produce hydrogen at 500mA cm -2 However, most of the catalysts working in neutral electrolytes reported in the literature only show the ability to operate continuously at small current densities. Therefore, research on hydrogen production under high current density in neutral water electrolysis should be continuously promoted. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a neutral electrocatalytic hydrogen evolution method in view of the deficiencies in the prior art. The present invention can be used for electrolyzing water to produce hydrogen in a neutral environment with a neutral electrolyte or neutral simulated seawater, has no problem of corrosion of the electrolysis device, and has the ability to work continuously at a higher current.
[0004] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0005] A neutral electrocatalytic hydrogen evolution method is disclosed. A cobalt-iron bimetallic phosphide nanosheet material is used as a hydrogen evolution working electrode, and neutral electrocatalytic hydrogen evolution is performed in a neutral electrolyte or neutral simulated seawater. The cobalt-iron bimetallic phosphide nanosheet material is prepared by taking iron salt and cobalt salt at an iron-cobalt molar ratio of 1:4-4:1, performing a hydrothermal reaction on a conductive substrate in an aqueous solution containing urea and ammonium fluoride, cooling to room temperature after the reaction, taking out, washing, and drying in an oven; placing sodium hypophosphite at an upstream position, placing a sheet-like cobalt-iron bimetallic layered hydroxide obtained by the hydrothermal reaction as a precursor at a downstream position of a tubular furnace, and preparing the material by a high-temperature phosphating method under an inert atmosphere; the cobalt-iron bimetallic phosphide nanosheet presents a nanosheet stacking structure and has good dispersibility; and the nanosheet is thin and smooth, with a thickness of 50-200 nm and a size of 2-3 μm.
[0006] According to the above scheme, the conductive substrate is any one of metal nickel foam, metal iron foam and carbon cloth; the concentration of the iron salt is 0.01-0.1 mol / L; the concentration of the cobalt salt is 0.015-0.15 mol / L; the concentration of the urea is 0.2-0.4 mol / L; the concentration of the ammonium fluoride is 0.1-0.3 mol / L; the molar ratio of cobalt atoms in the cobalt salt to iron atoms in the iron salt is preferably 2:3-3.5:1.5, more preferably 3:2.
[0007] According to the above scheme, the neutral electrolyte is any one of phosphate buffer, sodium sulfate and potassium carbonate, and the concentration of the neutral medium is 1-6 mol / L.
[0008] According to the above scheme, the neutral simulated seawater is a mixed aqueous solution of phosphate buffer and sodium chloride. The concentration of the phosphate buffer is 1 mol / L, and the concentration of the sodium chloride is 0.5 mol / L.
[0009] According to the above scheme, the hydrothermal reaction temperature is 100-200°C, and the hydrothermal reaction time is 4-14h.
[0010] According to the above scheme, the iron salt is any one of Fe(NO3)3, Fe2(SO4)3 and FeCl3.
[0011] According to the above scheme, the cobalt salt is any one of Co(NO3)2, CoSO4 and CoCl2.
[0012] According to the above scheme, the high temperature phosphating method uses a heating rate of 2-5°C / min, a phosphating temperature of 300-400°C, and a phosphating time of 1-3h.
[0013] According to the above scheme, the cobalt-iron bimetallic phosphide nanosheet material is used as the hydrogen evolution working electrode, and the graphite rod is used as the counter electrode, and is placed in a three-electrode system for neutral electrocatalytic hydrogen evolution; or the cobalt-iron bimetallic phosphide nanosheet material is used as the hydrogen evolution working electrode, and the flaky cobalt-iron bimetallic layered hydroxide precursor is used as the oxygen evolution electrode, and a two-electrode system is used for neutral electrocatalytic hydrogen evolution.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] The neutral electrocatalytic hydrogen evolution method provided by the present invention is used for hydrogen evolution in neutral electrolyte or neutral simulated seawater, and exhibits excellent catalytic activity and stability: at 10, 100 and 400 mA / cm 2 At current densities of 10, 100, and 400 mA / cm, the required overpotentials in neutral electrolytes are as low as 90, 201, and 433 mV; at current densities of 10, 100, and 400 mA / cm 2At current densities of 200 mA / cm2, the overpotentials required in neutral simulated seawater are as low as 67, 179, and 416 mV, while in neutral solution at 500 mA / cm2 2 The device can operate stably for more than 400 hours at a constant current density of 300 and 500 mA / cm 2 The flaky cobalt-iron bimetallic layered hydroxide was used as the anode and the cobalt-iron bimetallic phosphide nanosheet was used as the cathode material to form a full water splitting device. In a neutral electrolyte, it only takes 2.0V to reach 100mA / cm 2 The current density can be stably operated for 50 hours.
[0016] The present invention can use the flaky cobalt-iron bimetallic layered hydroxide in the preparation process of the cobalt-iron bimetallic phosphide nanosheet material hydrogen evolution working electrode as an oxygen evolution catalyst with excellent performance, and obtain a neutral water electrolysis hydrogen evolution catalyst with excellent performance after phosphating. Through one preparation process, the cathode and the anode can be simultaneously obtained to construct a neutral electrocatalytic hydrogen evolution system for neutral electrocatalytic hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Scanning electron microscope (SEM) images of cobalt-iron bimetallic phosphide nanosheets (denoted as CoFeP / NF) grown on a nickel foam substrate after the electrodeposition process in Example 1 of the present invention at different magnifications.
[0018] Figure 2 The scanning electron microscope (SEM) images of the flaky cobalt-iron bimetallic layered hydroxide (denoted as CoFe-LDH / NF) in Example 1 of the present invention at different magnifications.
[0019] Figure 3 3 is the distribution diagram of Co, Fe and P elements of CoFeP / NF in Example 1 of the present invention.
[0020] Figure 4 (a) is a comparison of the X-ray diffraction patterns (XRD) of CoFeP / NF and CoFe-LDH / NF in Example 1 of the present invention, and (b) is a comparison of the X-ray diffraction patterns (XRD) of CoFeP / NF.
[0021] Figure 5The HER performance comparison diagram of CoFeP / NF in Example 1 of the present invention in a neutral electrolyte (1 mol / L PBS) and other samples is as follows: (a) linear sweep voltammetry (LSV) curve; (b) overpotential comparison diagram at different current densities; (c) Tafel slope diagram; (d) electrochemical impedance spectroscopy (EIS); (e) LSV curves of samples prepared at different Co / Fe precursor ratios; (f) overpotential comparison diagram of samples prepared at different Co / Fe precursor ratios.
[0022] Figure 6 The HER performance comparison diagram of CoFeP / NF in Example 1 of the present invention in a neutral simulated seawater electrolyte (1 mol / L PBS+0.5 mol / L NaCl) and other samples is shown: (a) linear sweep voltammetry (LSV) curve; (b) overpotential comparison diagram at different current densities.
[0023] Figure 7 This is the performance curve of CoFeP / NF in Example 1 of the present invention in a stable test under constant current density in a neutral electrolyte and a neutral simulated seawater electrolyte.
[0024] Figure 8 The performance curve (a) of the two-electrode electrolysis device composed of CoFeP / NF and CoFe-LDH / NF in Example 1 of the present invention in a neutral electrolyte and 100 mA cm -2 Stability test diagram under current density (b). DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A neutral electrocatalytic hydrogen evolution method comprises the following steps:
[0028] First, a 1.5cm*4cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 20 minutes and then dried as a conductive substrate for standby use; then a mixed solution of 0.02mol / L ferric nitrate, 0.03mol / L cobalt nitrate, 0.125mol / L ammonium fluoride and 0.25mol / L urea was prepared, and placed in a polytetrafluoroethylene reactor together with the treated nickel foam, and reacted at 120°C for 6h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 5h to obtain a sheet-like cobalt-iron bimetallic layered hydroxide precursor grown on nickel foam, recorded as CoFe-LDH / NF. Finally, the CoFe-LDH / NF precursor was loaded into a porcelain boat and placed downstream of the tube furnace. 0.5 g of sodium hypophosphite was loaded into a porcelain boat as a phosphorus source and placed upstream of the tube furnace. The temperature was increased from room temperature to 350°C at a heating rate of 3°C / min. The temperature was maintained at 350°C for 2 hours in an argon atmosphere. After cooling to room temperature, the final sample of cobalt-iron bimetallic phosphide nanosheets was obtained, which was recorded as CoFeP / NF.
[0029] Figure 1 and Figure 2 The SEM images of the prepared CoFeP / NF and CoFe-LDH / NF catalysts are shown in Figure 1. The specific steps are to observe the sample morphology of the prepared catalyst on JEOL JSM-7900, and the electron beam intensity is 12.6keV. It can be seen that CoFeP / NF presents a stacked structure of nanosheets, but the spatial distribution is good, the thickness of the nanosheets is 50-200nm, and the surface of the nanosheets is smooth; while CoFe-LDH / NF also has a stacked structure of nanosheets, but the sheets are thinner and smoother, indicating that phosphating has not changed the overall morphology of the CoFe-LDH / NF precursor.
[0030] Figure 3 The EDS element distribution diagram of the prepared CoFeP / NF catalyst shows that the Co, Fe and P elements are densely and evenly distributed on the nanosheet structure, indicating that the above preparation method can successfully phosphate CoFe-LDH / NF. Through SEM-EDS, it can be measured that the atomic percentages of Co, Fe and P are 31.97%, 31.64% and 36.39% respectively, and the atomic ratio of cobalt to iron is 1:1.
[0031] Figure 4The XRD spectra of the prepared CoFeP / NF and CoFe-LDH / NF catalysts are shown in the figure. The specific steps are to collect the XRD spectra of the prepared catalysts on X'Pert PRO. Comparing the spectra before and after phosphating, it is found that the diffraction peak of the CoFe-LDH phase disappears completely, indicating that the phosphating process can convert all CoFe-LDH into metal phosphides. The strongest diffraction peak excluding the diffraction peak of nickel foam belongs to the (111) crystal plane of Fe2P, and the (201)(002)(300)(211) crystal planes of Fe2P can be detected. The (131)(002)(230)(320) and other crystal planes of Co2P can be detected. Therefore, CoFeP / NF is a mixture phase of Fe2P and Co2P.
[0032] The cobalt-iron bimetallic phosphide nanosheet material was placed in a three-electrode system as the hydrogen evolution working electrode, the graphite rod as the counter electrode, the saturated calomel electrode as the reference electrode, the neutral aqueous electrolyte was 1 mol / L phosphate buffer, and the neutral simulated seawater electrolyte was a 0.5 mol / L sodium chloride solution added to the above neutral electrolyte. The sample was in a neutral aqueous electrolyte at 10, 100 and 400 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0033] Figure 5 (e) The study demonstrated the effect of different Co / Fe ratios on the neutral HER performance of the material, wherein the specific method for controlling different Co / Fe ratios is: regulating the ratio of cobalt atoms to iron atoms (specifically 1:4, 2:3, 3:2, 3.5:1.5, 4:1), and the rest of the synthesis conditions are consistent with Example 1. The results show that at a current density of 10 mA / cm2, the overpotentials of each ratio are 123, 102, 90, 110, and 124 mV, respectively. Materials prepared with different Co / Fe ratios have different neutral hydrogen evolution properties, which may be due to the different electronic structures of the materials prepared from precursors with different iron-cobalt atomic ratios. The optimal atomic ratio (the ratio of cobalt atoms to iron atoms is 3:2) has the most excellent electronic structure, not only has a suitable intermediate adsorption energy, but also can obtain excellent electron transfer ability, and has the best neutral water electrolysis hydrogen evolution activity. Specifically from Figure 5 As can be seen in (f), when the Co / Fe precursor ratio is 3 / 2, the neutral HER overpotential required for the prepared electrode is the lowest and the electrode has the best activity.
[0034] Figure 5(a), (b) and (c) further show the linear sweep voltammetry (LSV) curves, Tafel slopes, and detailed HER overpotential comparison diagrams of CoFeP / NF (the ratio of cobalt atoms to iron atoms is 3:2), CoFe-LDH / NF, Co2P / NF, Fe2P / NF, NF and commercial Pt / C samples in neutral electrolyte. It can be found that the formation of cobalt-iron bimetallic phosphide in Example 1 significantly improves the HER performance of cobalt and iron monometallic phosphides at 10, 100 and 400 mA / cm 2 At current densities of 200, 201, and 433 mV, the overpotential required in neutral is much lower than that of commercial Pt / C samples at high current densities. The Tafel slopes of these samples are further calculated as follows: Figure 5 The CoFeP / NF sample shown in (c) has a low Tafel slope of 83.63 mV / dec, indicating that the cobalt-iron bimetallic phosphide has a better neutral HER kinetics. At the same time, the formation of bimetallic phosphide helps to improve the conductivity of the material, thereby promoting rapid electron transfer on the catalyst, as shown in Figure 5 (d) The electrochemical impedance spectroscopy diagram shows the smaller charge transfer resistance of CoFeP / NF.
[0035] Figure 6 (a) and (b) show the LSV curves of CoFeP / NF, CoFe-LDH / NF, Co2P / NF, Fe2P / NF and NF samples in neutral simulated seawater electrolyte and detailed HER overpotential comparison diagrams. Due to the addition of additional 0.5 mol / L sodium chloride solution, the conductivity of the solution is enhanced. Therefore, compared with that in neutral electrolyte, the HER performance of each catalyst in neutral simulated seawater electrolyte is improved and the overpotential is lower. At 10, 100 and 400 mA / cm 2 At current densities of , the overpotentials of water HER are 67, 179, and 416 mV.
[0036] Figure 7 (a) shows the CoFeP / NF sample in a neutral electrolyte (1 mol / L PBS) at 500 mA / cm 2 The stability test chart of current density shows that the performance only decayed by 10% after 450 hours of operation. Figure 7 (b) shows the stability test of the sample in neutral simulated seawater electrolyte (1 mol / L PBS + 0.5 mol / L NaCl) at 300 and 500 mA / cm 2 It runs stably for 125h under current density conditions.
[0037] Figure 8(a) shows the LSV curve of the two-electrode electrolytic cell with CoFeP / NF as cathode and CoFe-LDH / NF as anode in neutral electrolyte, reaching 100 mA / cm 2 The current density only requires 2.0 V. 8(b) shows that they can 2 The stability test diagram under current density. The flaky cobalt-iron bimetallic layered hydroxide prepared by the present invention can be used as a water oxidation catalyst with excellent performance, and after phosphating, a neutral water electrolysis hydrogen evolution catalyst with excellent performance can be obtained. The cathode and anode can be obtained simultaneously through a preparation process for neutral electrocatalytic hydrogen evolution.
[0038] Example 2
[0039] A neutral electrocatalytic hydrogen evolution method comprises the following steps:
[0040] First, place the 1.5cm*4cm metal iron foam in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 20 minutes and then dry it as a conductive substrate for use; then prepare 60mL of a mixed solution of 0.01mol / L ferric sulfate, 0.015mol / L cobalt sulfate, 0.1mol / L ammonium fluoride and 0.2mol / L urea, and place it in a polytetrafluoroethylene reactor together with the treated metal nickel foam, and react at 100℃ for 4h using a hydrothermal method. After the reaction is completed and cooled to room temperature, rinse it repeatedly with anhydrous ethanol and deionized water, and then dry it in an oven set at 60℃ for 5h to obtain a flaky cobalt-iron bimetallic layered hydroxide precursor grown on the iron foam, recorded as CoFe-LDH / IF. Finally, the CoFe-LDH / IF precursor was loaded into a porcelain boat and placed downstream of the tube furnace. 0.3 g of sodium hypophosphite was loaded into a porcelain boat as a phosphorus source and placed upstream of the tube furnace. The temperature was raised from room temperature to 300°C at a heating rate of 3°C / min. The temperature was maintained at 300°C for 2 hours in an argon atmosphere. After cooling to room temperature, the final sample of cobalt-iron bimetallic phosphide nanosheets was obtained, which was recorded as CoFeP / IF.
[0041] The cobalt-iron bimetallic phosphide nanosheet material was placed in a three-electrode system as the hydrogen evolution working electrode, a graphite rod as the counter electrode, a saturated calomel electrode as the reference electrode, and a neutral aqueous electrolyte of 1 mol / L sodium sulfate. The sample was subjected to 10, 100, and 400 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0042] Example 3
[0043] A neutral electrocatalytic hydrogen evolution method comprises the following steps:
[0044] First, a 3.0cm*4cm carbon cloth was soaked in a mixed acid of 10% nitric acid and sulfuric acid (nitric acid: sulfuric acid is 3:1), and finally ultrasonically cleaned in anhydrous ethanol and deionized water for 20 minutes and dried as a conductive substrate for standby use; then a mixed solution of 0.04mol / L ferric chloride, 0.06mol / L cobalt chloride, 0.15mol / L ammonium fluoride, and 0.3mol / L urea was prepared, and placed in a polytetrafluoroethylene reactor together with the treated carbon cloth, and reacted at 140°C for 8h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 5h to obtain a flaky cobalt-iron bimetallic layered hydroxide precursor grown on the carbon cloth, recorded as CoFe-LDH / CC. Finally, the CoFe-LDH / CC precursor was loaded into a porcelain boat and placed downstream of the tube furnace. 0.5 g of sodium hypophosphite was loaded into a porcelain boat as a phosphorus source and placed upstream of the tube furnace. The temperature was increased from room temperature to 350°C at a heating rate of 3°C / min. The temperature was maintained at 350°C for 1 hour in an argon atmosphere. After cooling to room temperature, the final sample of cobalt-iron bimetallic phosphide nanosheets was obtained, which was recorded as CoFeP / CC.
[0045] The cobalt-iron bimetallic phosphide nanosheet material was placed in a three-electrode system as the hydrogen evolution working electrode, a graphite rod as the counter electrode, a saturated calomel electrode as the reference electrode, and a neutral aqueous electrolyte of 3 mol / L phosphate buffer. The sample was subjected to 10, 100, and 400 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0046] Example 4
[0047] A neutral electrocatalytic hydrogen evolution method comprises the following steps:
[0048] First, a 1.5cm*4cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 20 minutes and then dried as a conductive substrate for standby use; then 60mL of a mixed solution of 0.06mol / L ferric nitrate, 0.09mol / L cobalt nitrate, 0.2mol / L ammonium fluoride and 0.34mol / L urea was prepared and placed in a polytetrafluoroethylene reactor together with the treated nickel foam, and reacted at 160°C for 10h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 5h to obtain a flaky cobalt-iron bimetallic layered hydroxide precursor grown on nickel foam, recorded as CoFe-LDH / NF. Finally, the CoFe-LDH / NF precursor was loaded into a porcelain boat and placed downstream of the tube furnace. 0.7 g of sodium hypophosphite was loaded into a porcelain boat as a phosphorus source and placed upstream of the tube furnace. The temperature was raised from room temperature to 300°C at a heating rate of 3°C / min. The temperature was maintained at 300°C for 2 hours in an argon atmosphere. After cooling to room temperature, the final sample of cobalt-iron bimetallic phosphide nanosheets was obtained, which was recorded as CoFeP / NF.
[0049] The cobalt-iron bimetallic phosphide nanosheet material was placed in a three-electrode system as the hydrogen evolution working electrode, a graphite rod as the counter electrode, a saturated calomel electrode as the reference electrode, and a neutral aqueous electrolyte of 5 mol / L phosphate buffer. The sample was subjected to 10, 100, and 400 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0050] Example 5
[0051] A neutral electrocatalytic hydrogen evolution method comprises the following steps:
[0052] First, a 1.5cm*4cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 20 minutes and then dried as a conductive substrate for standby use; then a mixed solution of 0.08mol / L ferric sulfate, 0.12mol / L cobalt nitrate, 0.25mol / L ammonium fluoride and 0.37mol / L urea was prepared, and placed in a polytetrafluoroethylene reactor together with the treated nickel foam, and reacted at 180°C for 12h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 5h to obtain a flaky cobalt-iron bimetallic layered hydroxide precursor grown on nickel foam, recorded as CoFe-LDH / NF. Finally, the CoFe-LDH / NF precursor was loaded into a porcelain boat and placed downstream of the tube furnace. 0.9 g of sodium hypophosphite was loaded into a porcelain boat as a phosphorus source and placed upstream of the tube furnace. The temperature was raised from room temperature to 350°C at a heating rate of 3°C / min. The temperature was maintained at 350°C for 2 hours in an argon atmosphere. After cooling to room temperature, the final sample of cobalt-iron bimetallic phosphide nanosheets was obtained, which was recorded as CoFeP / NF.
[0053] The cobalt-iron bimetallic phosphide nanosheet material was placed in a three-electrode system as the hydrogen evolution working electrode, a graphite rod as the counter electrode, a saturated calomel electrode as the reference electrode, and a neutral aqueous electrolyte of 6 mol / L potassium carbonate. The sample was subjected to 10, 100, and 400 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0054] Example 6
[0055] A neutral electrocatalytic hydrogen evolution method comprises the following steps:
[0056] First, a 1.5cm*4cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 20 minutes and then dried as a conductive substrate for standby use; then 60mL of a mixed solution of 0.1mol / L ferric chloride, 0.15mol / L cobalt sulfate, 0.3mol / L ammonium fluoride and 0.4mol / L urea was prepared and placed in a polytetrafluoroethylene reactor together with the treated nickel foam, and reacted at 200°C for 14h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 5h to obtain a sheet-like cobalt-iron bimetallic layered hydroxide precursor grown on nickel foam, recorded as CoFe-LDH / NF. Finally, the CoFe-LDH / NF precursor was loaded into a porcelain boat and placed downstream of the tube furnace. 1.2 g of sodium hypophosphite was loaded into a porcelain boat as a phosphorus source and placed upstream of the tube furnace. The temperature was raised from room temperature to 400°C at a heating rate of 3°C / min. The temperature was maintained at 400°C for 3 hours in an argon atmosphere. After cooling to room temperature, the final sample of cobalt-iron bimetallic phosphide nanosheets was obtained, which was recorded as CoFeP / NF.
[0057] The cobalt-iron bimetallic phosphide nanosheet material was placed in a three-electrode system as the hydrogen evolution working electrode, a graphite rod as the counter electrode, a saturated calomel electrode as the reference electrode, and a neutral aqueous electrolyte of 6 mol / L phosphate buffer. The sample was subjected to 10, 100, and 400 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0058] Table 1 Summary of the neutral medium water reduction performance of cobalt-iron bimetallic phosphide nanosheets prepared in different embodiments.
[0059] Table 1
[0060]
[0061]
[0062] In summary, the formation of the bimetallic phosphide of the present invention optimizes the original electronic structure, improves the electrical conductivity and electron transfer ability of the material, enriches the active sites, promotes the kinetics of the hydrogen evolution reaction, and thus significantly improves the neutral electrocatalytic hydrogen evolution performance of the material.
[0063] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A neutral electrocatalytic hydrogen evolution method, characterized in that: A cobalt-iron bimetallic phosphide nanosheet material is used as a hydrogen evolution working electrode, and neutral electrocatalytic hydrogen evolution is carried out in a neutral electrolyte or neutral simulated seawater. The cobalt-iron bimetallic phosphide nanosheet material is prepared by taking iron salt and cobalt salt at an iron-cobalt molar ratio of 1:4-4:1, carrying out a hydrothermal reaction on a conductive substrate in an aqueous solution containing urea and ammonium fluoride, cooling to room temperature after the reaction, taking out, washing, and drying in an oven; placing sodium hypophosphite at an upstream position, placing the flaky cobalt-iron bimetallic layered hydroxide obtained by the hydrothermal reaction as a precursor at a downstream position of a tubular furnace, and preparing the material by a high-temperature phosphating method under an inert atmosphere; the cobalt-iron bimetallic phosphide nanosheet presents a nanosheet stacking structure and has good dispersibility; the nanosheet is thin and smooth, with a thickness of 50-200nm and a size of 2-3μm.
2. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The conductive substrate is any one of metal nickel foam, metal iron foam and carbon cloth; the concentration of the iron salt is 0.01-0.1 mol / L; the concentration of the cobalt salt is 0.015-0.15 mol / L; the concentration of the urea is 0.2-0.4 mol / L; the concentration of the ammonium fluoride is 0.1-0.3 mol / L; the molar ratio of cobalt atoms in the cobalt salt to iron atoms in the iron salt is 2:3-3.5:1.
5.
3. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The molar ratio of cobalt atoms in the cobalt salt to iron atoms in the iron salt is 3:
2.
4. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The neutral electrolyte is any one of phosphate buffer, sodium sulfate and potassium carbonate, and the concentration of the neutral medium is 1-6 mol / L.
5. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The neutral simulated seawater is a mixed aqueous solution of phosphate buffer and sodium chloride.
6. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The hydrothermal reaction temperature is 100-200° C., and the hydrothermal reaction time is 4-14 hours.
7. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The iron salt is any one of Fe(NO3)3, Fe2(SO4)3 and FeCl3.
8. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The cobalt salt is any one of Co(NO3)2, CoSO4 and CoCl2.
9. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: The high temperature phosphating method uses a heating rate of 2-5°C / min, a phosphating temperature of 300-400°C, and a phosphating time of 1-3h.
10. The neutral electrocatalytic hydrogen evolution method according to claim 1, characterized in that: Cobalt-iron bimetallic phosphide nanosheet material is used as the hydrogen evolution working electrode, and a graphite rod is used as the counter electrode, and is placed in a three-electrode system for neutral electrocatalytic hydrogen evolution; or cobalt-iron bimetallic phosphide nanosheet material is used as the hydrogen evolution working electrode, and a flaky cobalt-iron bimetallic layered hydroxide is used as the oxygen evolution electrode, and a two-electrode system is used for neutral electrocatalytic hydrogen evolution.